PCOS and Role of Cumulus Gene Expression in Assessing Oocytes Quality - Sayutti, Nurainie; Abu, Muhammad Azrai; Ahmad, Mohd Faizal (Frontiers in Endocrinology, 2022)
The global infertility rate has been declining every year and polycystic ovarian syndrome (PCOS) ranks highest among the treatable anovulatory infertility cause. Nevertheless, the success rate of treatment and live-birth outcome following assisted reproductive technique (ART) remains poor. A critical step in ART is the assessment of oocyte and embryo quality. However, this same procedure may also cause harm. Identification of potential biomarkers especially in the cumulus cell oocyte complex will help to predict the outcome and may create space for improvement. This review will explain the basis of folliculogenesis, the role of cumulus cells and summarize the results from cumulus cells gene analysis, considering the possibilities of using it as markers for oocyte quality/embryo competence and clinical outcome.